F-contractions of Hardy–Rogers type and application to multistage decision - Vetro, Francesca (Nonlinear Analysis: Modelling and Control, 2016)
We prove fixed point theorems for F-contractions of Hardy–Rogers type involving self-mappings defined on metric spaces and ordered metric spaces. An example and an application to multistage decision processes are given to show the usability of the obtained theorems.
Keywords: F-contractions of Hardy–Rogers type and application to multistage decision processes